2010
DOI: 10.1080/09540120903196883
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children living in HIV/AIDS-affected families in rural areas in Yunnan, China

Abstract: The aim of this study was to explore the main influencing factors of the health related quality of life (HRQL) of children living in HIV/AIDS-affected families in rural areas in Yunnan, China. The HRQL of 116 children aged 8 to 17 from HIV/AIDS-affected families and of 109 children from unaffected families was evaluated by the Chinese Version of PedsQL TM 4.0. Some potential influencing factors were investigated, such as demographic characteristics, the families' social and economic status, foster models, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Results of this study is similar to the study carried out in four townships of Longchuan County in Yunnan [6] and study of caregivers of HIV infected children in Thailand [5] This study is conducted among is limited to children who are attending to ART Plus centre of one of the Districts. Studying all children who were diagnosed to have HIV irrespective of ART treatment may give more information about their quality of life and social support.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Results of this study is similar to the study carried out in four townships of Longchuan County in Yunnan [6] and study of caregivers of HIV infected children in Thailand [5] This study is conducted among is limited to children who are attending to ART Plus centre of one of the Districts. Studying all children who were diagnosed to have HIV irrespective of ART treatment may give more information about their quality of life and social support.…”
Section: Discussionsupporting
confidence: 77%
“…Caregivers of children from affected families reported lower scores than those from unaffected families. This study reported that children suffered from HIV had lower score on HRQL than those from unaffected families [6].…”
Section: Introductionmentioning
confidence: 62%
“…Some cross-sectional studies indicated that disclosure was associated with lower emotional and social functioning [58], more externalizing symptoms [33], and higher depression score [3] among children. However, other cross-sectional surveys suggested that disclosure was not significantly related to children’s psychological outcomes including externalizing problems [3, 35, 59], internalizing behaviors [3, 33, 35], anxiety [3], depression [59], adaptive functioning [29] or school grades [59].…”
Section: Resultsmentioning
confidence: 99%
“…In China, studies suggest that children affected by HIV are subjected to high level of stigmatization (Chi, Li, Zhao, & Zhao, 2013;Lin et al, 2010). They also report higher levels of psychosocial problems such as loneliness, low self-esteem and more depressive symptoms Zhao et al, 2007Zhao et al, , 2009), sleep problems (Zhao et al, 2007), lower quality of life (Xu, Wu, Rou, Duan, & Wang, 2010), poorer school performance (Ji et al, 2007), and unmet basic needs such as food, shelter, education, and medical care (Zhao et al, 2007).…”
Section: Psychosocial Health Of Children Of Parents With Hivmentioning
confidence: 98%